Positivity Proportion of Xpert MTB/RIF in Suspected Pediatric Pulmonary Tuberculosis Patients at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia - Salsabila, Sabila; Mertaniasih, Ni Made; Setyoningrum, Retno Asih (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2025)
Highlights: This study utilized Xpert MTB/RIF result data from children using both sputum and gastric lavage specimens, which is different from previous studies that relied solely on sputum specimens. “Mycobacterium tuberculosis not detected” was the most common result on the Xpert MTB/RIF examination in suspected pediatric TB cases.   Abstract Introduction: The difficulty of diagnosing tuberculosis (TB) is the most significant challenge in pediatric pulmonary TB cases. More accurate and faster diagnostic tools are essential for detecting TB infections, enabling the implementation of appropriate therapy and treatment management more effectively and promptly. This study aimed to determine the proportion of positive results using the Xpert Mycobacterium tuberculosis/rifampicin (MTB/RIF) assay as a rapid molecular method in suspected pediatric pulmonary TB patients at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. Methods: This study employed a descriptive-retrospective design, utilizing data obtained from medical records. The total number of samples included in this study was 373 samples (n=373). The data was analyzed using the International Business Machines Corporation (IBM) Statistical Package for the Social Sciences (SPSS) version 26.0 for Windows. Results: The most commonly used specimen from pediatric TB patients in the Xpert MTB/RIF examination was sputum, accounting for 59.2%. The most common result from the Xpert MTB/RIF examination was “MTB not detected,” with a prevalence of 88.2%. Conclusion: The most commonly used specimen for the Xpert MTB/RIF examination of pediatric pulmonary TB was sputum. The majority of results found with the Xpert MTB/RIF examination were “MTB not detected” both in sputum and gastric aspirate specimens.